Relationship between serum anion gap and mortality in ICU in multiple myeloma patients in the MIMIC database: A retrospective cohort study - Qianhui Wang; Pengyu Hu; Haibo Cong (PLoS ONE, 2025)
Background Serum anion gap has diagnostic value in patients with multiple myeloma, but its association with ICU mortality and threshold value remain unclear. Methods Multiple myeloma patients meeting criteria were selected from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. The exposure factor was serum anion gap, and the outcome was ICU in-hospital mortality. Multivariable-adjusted Cox regression, curve fitting, and forest plots were used to evaluate the relationship between anion gap and ICU mortality in multiple myeloma patients. Results A total of 323 eligible subjects were included (206 males [63.8%], 117 females [36.2%]). Multivariable Cox regression showed that each 1-unit increase in AG was associated with a 7% increased mortality risk (HR = 1.07, 95%CI = 1.01–1.14, P = 0.032). Curve fitting revealed a nonlinear relationship between anion gap and ICU mortality (nonlinear P = 0.038), with the lowest risk at 15.29 mmol/L. Incorporating AG into traditional risk factor models improved mortality prediction (P = 0.038). Conclusion Serum anion gap exhibits a nonlinear relationship with ICU mortality in multiple myeloma patients, with the lowest risk observed at approximately 15.29 mmol/L.